Exploring Language Repertoire in EFL Classroom Interaction - Rendi Afriadi (Rumah Jurnal IAIN Bukittinggi, 2021)
As EFL classroom interaction mostly occur in multilingual or at least bilingual settings, classroom participants has already had languages other than English as part of their language repertoire. They use these languages in their daily life, and oftentimes they are also brought to the classroom interaction. However, some suggests that the ideal EFL classroom is the one where the target language should be fully used. Thus, the practice of using students’ L1 should be discouraged, banned, or at least minimized. Meanwhile, the current trends have challengged this notion by asserting the fact monolingual classroom might be seem a bit unrealistic, especially for low level students, and students’ L1 can be utilized in the clasrrom to help them during the process. This study aims to explore how students’ language repertoire is exploited during the classroom interaction and what functions it serves in the process. To obtain the data on this talk, some EFL classroom meetings were recorded and transcribed. The transcribed data were then analyzed to classify the language repertoire used and to identify its function. The analysis reveals that the language repertoire used in the classroom interaction are varied encompassing the national language, local language, and target language, and each repertoire serves different purposes. Keywords: EFL, classroom interaction, language repertoire